Analysis of Climate-Net Unit Generated (NUG) Relationship for the Hydroelectric Power Station - Azreen Harina, Azman; Nurul Nadrah Aqilah, Tukimat; M. A., Malek (Springer Singapore, 2020)
Global climate change has influenced the sustainability of hydroelectric power generation caused by the uncertainties of the air temperature and rainfall pattern. Current reservoir water management practices may not be robust to survive impacts of climate changes particularly in sufficiency of long term water demand-supply. In addition, the electricity demand is also increasing year by year because of extreme daily weather. Higher temperature will increase the electricity demand which is good income generation however this has resulted high operation cost and reduction of water storage. Therefore, the main objective of the study was to determine the relationship between climate change with net unit generated (NUG) at Sultan Mahmud Hydro Electric Power Station. To achieve the objective, a Statistical Downscaling Model (SDSM) was applied to identify the best atmospheric variables which influenced the long term climate formation at the area. The climate-NUG relationship had been analyzed based on statistical equation. The finding shows inversed proportional relationships between rainfall and temperature. During wet seasons, the maximum rainfall achieved 60mm/month and the temperature recorded was around 26◦C. Minimum rainfall recorded during dry seasons was <10mm/month with maximum temperature reading up to 28.5◦C. In terms of power generated, the maximum NUG data were often recorded in wet season. The highest NUG recorded during dry seasons were 1 000 000-300 000 000 kWh while the value of NUG during wet seasons were 50 000 000-240 000 000 kWh.